STAGES OF DEVELOPMENT OF THE FRUIT AND VEGETABLE GROWING INDUSTRY IN THE SOUTHERN SURKHANDARYA REGION OF UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2026)
In this article, the stages of formation and development of the “Fruit and vegetable farming” branch of agriculture in the southern Surkhandarya region of Uzbekistan are analyzed based on scientific sources, conclusions and suggestions are given.